1967
DOI: 10.1017/s0031182000071857
|View full text |Cite
|
Sign up to set email alerts
|

The route of migration of Eimeria stiedae (Lindemann, 1865) sporozoites between the duodenum and bile ducts of the rabbit

Abstract: Young rabbits were infected by mouth with sporulated Eimeria stiedae oocysts and killed at 1, 3, 5, 8, 12, 16, 24, 30, 48, 54, 72, 84, and 96 h after infection. Sporozoites were found in the lamina propria of the duodenum between 5 and 8 h after infection. Sporozoites were present in the mesenteric lymph nodes, both free and within lymphatic monocytes at between 12 and 84 h after infection. No sporozoites were observed in duodenal portal blood. These observations provide morphological evidence compatible with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Smetana (1933a) considered the possibility of traffic via the portal vein as well as the lymphatic system. Several authors (Smetana 1933a, Horton 1967, Fitzgerald 1970, Pellérdy and Dürr 1970 found sporozoites of E. stiedai within lymphoid cells in MLN. The way of their further migration is unclear.…”
Section: Migration Of Sporozoitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smetana (1933a) considered the possibility of traffic via the portal vein as well as the lymphatic system. Several authors (Smetana 1933a, Horton 1967, Fitzgerald 1970, Pellérdy and Dürr 1970 found sporozoites of E. stiedai within lymphoid cells in MLN. The way of their further migration is unclear.…”
Section: Migration Of Sporozoitesmentioning
confidence: 99%
“…The way of their further migration is unclear. Horton (1967) and Fitzgerald (1970) suppose that the sporozoites may be transported to the liver via the blood, but Dürr (1972) assumes the transport of sporozoites from MLN to blood is improbable and supposes that the parasite cells are spread throughout the whole host organism and after this they settle in the liver. This hypothesis is corroborated by the finding of sporozoites in bone marrow and measurement of radioactivity after infection with radioactive-labelled sporozoites (Dürr 1972).…”
Section: Migration Of Sporozoitesmentioning
confidence: 99%
“…The mechanism by which sporozoites gained access to these sites of infection was not determined. However, Horton (1967) andDiJrr (1972) suggested that sporozoites of Eimeria stiedai are carried to the liver by lymphatic monocytes. A similar mechanism may exist for the transport of Caryospora spp.…”
Section: Introductionmentioning
confidence: 99%
“…with regard to life cycles in their hosts, were also genetically separated from these Eimeria spp. To further elucidate the relationships between biological features and phylogenic positions, genetical examinations of a few other extraintestinal coccidia such as E. truncata (renal coccidiosis of goose) (Gomis et al 1996), E. neitzi (uterine coccidiosis of impala) (McCully et al 1970) or E. stiedai (liver coccidiosis of rabbit) (Horton 1967) are needed. gruis and E. reichenowi isolates in the present study, other Eimeria spp.…”
mentioning
confidence: 99%